Evaluation of a urology specialist therapeutic radiographer implemented radiotherapy pathway for prostate cancer patients. Issue 2 (May 2021) - Alexander, S.E.; Booth, L.; Delacroix, L.; Gordon, A.; Kirkpatrick, N.; Tree, A.C.
Abstract: Introduction: The role of the Urology Specialist Therapeutic Radiographer (USTR) was introduced to support a busy NHS uro-oncology practice. Key objectives were to improve patient preparedness for and experience of radiotherapy, focussed on prostate cancer. Pre-radiotherapy information seminars were developed, and on-treatment patient review managed by the USTRs. To evaluate the revamped patient pathway and direct further improvements, a patient experience survey was designed. Methods: An 18-point patient questionnaire was produced. The questionnaire captured patient experience and preparedness; pre, during and at completion of treatment. The patient population comprised men receiving radiotherapy for primary prostate cancer within one UK Trust. Results: Two-hundred and fifty-one responses were received. Seventy-three percent of patients felt completely prepared for radiotherapy, higher in those who attended a seminar (77%) compared to those who did not (61%). Eighty-nine and eighty-six percent of respondents were completely satisfied with verbal and written information received prior to commencing radiotherapy respectively. Seventy-three percent of responders would have found additional resources helpful. With respect to on-treatment clinics; eighty-five percent were seen on time or within 20 minutes, eighty-three percent felt fully involved in decisions regarding their care and ninety-one percent reported complete satisfaction with the knowledge of the health care professional reviewing them. The follow-up process was completely understood by eighty-eight percent and overall patient experience rated excellent by eighty-five percent of responders. Conclusion: The revamped pathway implemented by USTRs has achieved high levels of satisfaction at all stages of the prostate patient's radiotherapy. By diversifying the format of information giving, the USTRs hope to further meet the information needs of patients. Implications for practice: Validation of a prostate cancer radiotherapy pathway which employs USTRs and utilises a patient preparation seminar. This model could support the introduction of Specialist Therapeutic Radiographers in other Trusts and treatment sites.